This is a "trick stuff" in Maths which quite interesting. Hope that anyone will enjoy it.

Assume : A = B

=> A^2 = AB (multiply both by A)

=> A^2 - B^2 = AB - B^2 (take away both to B^2)

=> (A-B)(A+B)= B (A-B)

=> A+B = B

=> 2B = B (hence A = B)

=> 2 = 1

=> 1 + 1 = 1 BINGO !!!

I think we shouldn't study Maths anymore cause It's all wrong now ...

## 1 + 1 = 1 ? ? ? relaxing ...

### Jammie1000000

Posted 29 November 2007 - 01:31 PM

This is a "trick stuff" in Maths which quite interesting. Hope that anyone will enjoy it.

Assume : A = B

=> A^2 = AB (multiply both by A)

=> A^2 - B^2 = AB - B^2 (take away both to B^2)

=>

=> A+B = B

=> 2B = B (hence A = B)

=> 2 = 1

=> 1 + 1 = 1 BINGO !!!

I think we shouldn't study Maths anymore cause It's all wrong now ...

Assume : A = B

=> A^2 = AB (multiply both by A)

=> A^2 - B^2 = AB - B^2 (take away both to B^2)

=>

**(A-B)(A+B)**= B (A-B)=> A+B = B

=> 2B = B (hence A = B)

=> 2 = 1

=> 1 + 1 = 1 BINGO !!!

I think we shouldn't study Maths anymore cause It's all wrong now ...

(A-B)=0 so you cannot divide through by (A-B) as you cannot divide by 0

### cK_hoangan

Posted 29 November 2007 - 01:45 PM

Well-done !!!!

as I said, it's all for relaxing : D

You wanna try once more with 1 > 4 ? I will prove it soon

as I said, it's all for relaxing : D

You wanna try once more with 1 > 4 ? I will prove it soon

### Marcus

Posted 06 January 2008 - 04:01 PM

just to go along the same lines of posting bizarre mathematics, here is a proof that or in fact any number you want

eqn 1) x+1 = 0

eqn 2) 2x+2 = 0

divide eqn 2 by eqn 1

cancel the x+1 on top and bottom to get:

but this = anything helps prove the above problem...

=> (A-B)(A+B)= B (A-B) , (A-B) = 0

=> 0(A+B)= 0B

=>2B = B

so if =2

then this works XD XD

eqn 1) x+1 = 0

eqn 2) 2x+2 = 0

divide eqn 2 by eqn 1

cancel the x+1 on top and bottom to get:

but this = anything helps prove the above problem...

=> (A-B)(A+B)= B (A-B) , (A-B) = 0

=> 0(A+B)= 0B

=>2B = B

so if =2

then this works XD XD

### ad absurdum

Posted 07 January 2008 - 07:44 PM

Here's a tough one (you'll need to have done complex numbers, can't remember when it comes up in advanced higher):

Where's the error?

Where's the error?

### Wildespleen

Posted 21 January 2009 - 08:13 PM

Can I just confirm that e^2ipi is indeed one? I presume it originates from 'e^ipi + 1 = 0'? (Which we haven't really covered in class so far, we only mentioned it).

I've puzzled over this one for a while now and the only real possible fault I, personally, can find is this. Failing that, I fear the textbooks will have to be rewritten-> 1+1=1 and 2+2=2! There'll be anarchy in the streets! XD

I've puzzled over this one for a while now and the only real possible fault I, personally, can find is this. Failing that, I fear the textbooks will have to be rewritten-> 1+1=1 and 2+2=2! There'll be anarchy in the streets! XD

### Marcus

Posted 27 January 2009 - 02:12 PM

QUOTE (Wildespleen @ Jan 21 2009, 08:13 PM) <{POST_SNAPBACK}>

Can I just confirm that e^2ipi is indeed one? I presume it originates from 'e^ipi + 1 = 0'? (Which we haven't really covered in class so far, we only mentioned it).

I've puzzled over this one for a while now and the only real possible fault I, personally, can find is this. Failing that, I fear the textbooks will have to be rewritten-> 1+1=1 and 2+2=2! There'll be anarchy in the streets! XD

I've puzzled over this one for a while now and the only real possible fault I, personally, can find is this. Failing that, I fear the textbooks will have to be rewritten-> 1+1=1 and 2+2=2! There'll be anarchy in the streets! XD

Yeah , and it comes from Euler's formula: (only briefly mentioned in AH)

I had to ask my uni profs to explain what is wrong with this proof...

### Monkey Man

Posted 02 January 2010 - 06:50 PM

QUOTE Jammie1000000

QUOTE(cK_hoangan @ Nov 28 2007, 10:29 PM) View Post

This is a "trick stuff" in Maths which quite interesting. Hope that anyone will enjoy it.

Assume : A = B

=> A^2 = AB (multiply both by A)

=> A^2 - B^2 = AB - B^2 (take away both to B^2)

=> (A-B)(A+B)= B (A-B)

=> A+B = B

=> 2B = B (hence A = B)

=> 2 = 1

=> 1 + 1 = 1 blink.gif BINGO !!!

I think we shouldn't study Maths anymore cause It's all wrong now ... tongue.gif

(A-B)=0 so you cannot divide through by (A-B) as you cannot divide by 0

cool.gif

can i just add that this is not dividing through by (A-B), they cancel each other out

QUOTE(cK_hoangan @ Nov 28 2007, 10:29 PM) View Post

This is a "trick stuff" in Maths which quite interesting. Hope that anyone will enjoy it.

Assume : A = B

=> A^2 = AB (multiply both by A)

=> A^2 - B^2 = AB - B^2 (take away both to B^2)

=> (A-B)(A+B)= B (A-B)

=> A+B = B

=> 2B = B (hence A = B)

=> 2 = 1

=> 1 + 1 = 1 blink.gif BINGO !!!

I think we shouldn't study Maths anymore cause It's all wrong now ... tongue.gif

(A-B)=0 so you cannot divide through by (A-B) as you cannot divide by 0

cool.gif

can i just add that this is not dividing through by (A-B), they cancel each other out